Early detection system for psychological wellbeing among students in NTU EEE - Wong, Erwin Yong-Zhi (Nanyang Technological University, 2020)
In NTU, there are many great resources that can support students in their mental health throughout their season in university. However, oftentimes these resources are either scattered across various NTU platforms or cluttered through the single email channel. In addition, there is a huge barrier between students and counselling services within campus.This project aims to link students up with resources that will benefit them according to their needs. The execution will be through a hybrid chatbot where students first face a natural language chatbot, and can connect directly to a counsellor if required. This project is self-pitched to my FYP supervisor and the possibilities and requirements of the system evolved over the months. The current system is live on www.KarenBot.co. A Final Year Project demonstration video can be found on https://youtu.be/VY87nSiT3Bo(Closed Captions available).